Probing for primary functions of prohibitin in Trypanosoma brucei - Týc, Jirí; Faktorová, Drahomíra; Kriegová, Eva; Jirků, Milan; Vávrová, Zuzana; Maslov, Dmitri A; Lukes, Julius (International journal for parasitology, 2010)
Prohibitins (PHBs) 1 and 2 are small conserved proteins implicated in a number of functions in the mitochondrion, as well as in the nucleus of eukaryotic cells. The current understanding of PHB functions comes from studies of model organisms such as yeast, worm and mouse, but considerable debate remains with regard to the primary functions of these ubiquitous proteins. We exploit the tractable reverse genetics of Trypanosoma brucei, the causative agent of African sleeping sickness, in order to specifically analyse the function of PHB in this highly divergent eukaryote. Using inducible RNA interference (RNAi) we show that PHB1 is essential in T. brucei, where it is confined to the cell's single mitochondrion forming a high molecular weight complex. PHB1 and PHB2 appear to be indispensible for mitochondrial translation. Their ablation leads to a decrease in mitochondrial membrane potential, however no effect on the level of reactive oxygen species was observed. Flagellates lacking either PHB1 or both PHB1 and PHB2 exhibit significant morphological changes of their organelle, most notably its inflation. Even long after the loss of the PHB proteins, mtDNA was unaltered and mitochondrial cristae remained present, albeit displaced to the periphery of the mitochondrion, which is in contrast to other eukaryotes.
Keywords: messenger RNA; membránové potenciály; prohibitiny; mitochondrie; RNA interference; Prohibitins; represorové proteiny; RNA Interference; DNA, Mitochondrial; Repressor Proteins; protozoální proteiny; proteosyntéza; Membrane Potentials; Protein Biosynthesis; RNA, Messenger; zvířata; Protozoan Proteins; mitochondriální DNA; fylogeneze; Trypanosoma brucei brucei; Mitochondria; Phylogeny; Animals